2008
DOI: 10.1038/npp.2008.82
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Prepulse Inhibition and Executive Function by the COMT Inhibitor Tolcapone Depends on COMT Val158Met Polymorphism

Abstract: Recent evidence suggests that prepulse inhibition (PPI) levels relate to executive function possibly by a prefrontal cortex (PFC) dopamine (DA) link. We explored the effects of enhanced PFC DA signaling by the nonstimulant catechol-O-methyltransferase (COMT) inhibitor tolcapone, on PPI and working memory of subjects homozygous for the Val (low PFC DA) and the Met (high PFC DA) alleles of the COMT Val158Met polymorphism. Twelve Val/Val and eleven Met/Met healthy male subjects entered the study. Tolcapone 200 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
105
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 75 publications
(96 reference statements)
13
105
2
3
Order By: Relevance
“…It is possible that these findings reflect the existence of an inverted-U-shaped curve governing dopamine effects (Cools and D'Esposito, 2011), in which optimal dopaminergic tone can either be reached or "overdosed" by a drug that increases dopamine tone, depending on subjects' baseline dopamine levels. Consistent with this hypothesis, a behavioral study of prepulse inhibition demonstrated that subjects with a more active form of the COMT enzyme (and thus lower cortical dopamine tone) showed improved performance on tolcapone, but those with a less active form did not (Giakoumaki et al, 2008). Similarly, in a study of executive function, Apud et al (2007) found that subjects with a more active form of COMT showed greater improvements on tests of set shifting and verbal episodic memory when administered tolcapone.…”
Section: Discussionsupporting
confidence: 53%
“…It is possible that these findings reflect the existence of an inverted-U-shaped curve governing dopamine effects (Cools and D'Esposito, 2011), in which optimal dopaminergic tone can either be reached or "overdosed" by a drug that increases dopamine tone, depending on subjects' baseline dopamine levels. Consistent with this hypothesis, a behavioral study of prepulse inhibition demonstrated that subjects with a more active form of the COMT enzyme (and thus lower cortical dopamine tone) showed improved performance on tolcapone, but those with a less active form did not (Giakoumaki et al, 2008). Similarly, in a study of executive function, Apud et al (2007) found that subjects with a more active form of COMT showed greater improvements on tests of set shifting and verbal episodic memory when administered tolcapone.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, the tolcapone data mentioned above indicates that modification of the functioning of enzymes that degrade dopamine in the cerebral cortex change cognition. As variation in the COMT genotype has been shown to influence cognitive performance and response to pharmacological agents (as well as the effect of tolcapone: Giakoumaki et al (2008), it will be important to consider new developments in genetics when evaluating the possible benefits of new pharmacological cognitive enhancers.…”
Section: Neurotransmitters May Not Be the Viable Target For Cognitivementioning
confidence: 99%
“…Met/Met adults are thought to be near the apex of this curve, while Val carriers lay towards the lower end because of the increased dopamine metabolism rate associated with the Val allele (2,26,27).…”
Section: Introductionmentioning
confidence: 99%